The Effect Of Digitized Images On Developing The Artistic Production Of Primary School Students In Art Education (Journal of the College of Basic Education, 2024)
The research aims to identify the magnitude of the impact of digitized images on developing the artistic production of primary school students in the art education subject. The researchers chose the research sample in a random manner and it consisted of (30) fifth-grade students, divided into two groups. Division (A) represented the experimental group, with (15) students, and Division (B) represented the control group, with (15) students. The researchers adopted an experimental design with partial control for the two groups (experimental and control), and rewarded the two groups with the variables (age, father’s academic achievement, mother’s academic achievement, intelligence, previous experience (cognitive and skill test). The researchers prepared the research tool (the achievement test), which is the pre-test and the post-test. It verified the validity, reliability, difficulty factor, discriminating power, and effectiveness of the false alternatives.The experiment began on Wednesday, corresponding to (11/1/2023) for the two research groups (experimental and control) and ended on Wednesday, corresponding to (12/13/2023), and after the completion of the correction, the (Mann-Whitney test), (Smirnov) and (Pearson correlation equation) were used. To verify the differences between the two groups, the results reached by the researchers showed the superiority of the experimental group, which was studied using the method of digitized images, over the control group.